Crafting professionals: Logics of professional development in craft higher education. (April 2023) - England, Lauren
This article explores how the presence of competing logics in craft higher education (HE) influences educational provision and student experience. Findings are presented from four craft HE case studies across England, including analysis of degree programme specifications and module curricula and interviews with educators, current students and recent graduates conducted in 2018. The article presents how these logics influence employability-focused teaching in craft curricula and how this impacts time, space and facilities allocated to physical craft work. Key tensions identified include perceptions and measurement of graduate "success", the impact on skill development and studio space and (dis)engagement with professional development training. The article concludes with reflection on how this relates to the perceived value of arts degrees, but argues that the responsibility to "prepare" students for craft careers cannot lie solely with HE providers.